Efficacy of intranasal dexmedetomidine versus oral midazolam for paediatric premedication - Lakshmi Kumar; Ajay Kumar; Ramkumar Panikkaveetil; Bindu K Vasu; Sunil Rajan; Suresh G Nair (Indian Journal of Anaesthesia, 2017)
Background and Aims: Premedication is an integral component of paediatric anaesthesia which, when optimal, allows comfortable separation of the child from the parent for induction and conduct of anaesthesia. Midazolam has been accepted as a safe and effective oral premedicant. Dexmedetomidine is a selective alpha-2 agonist with sedative and analgesic effects, which is effective through the transmucosal route. We compared the efficacy and safety of standard premedication with oral midazolam versus intranasal dexmedetomidine as premedication in children undergoing elective lower abdominal surgery. Methods: This was a prospective randomised double-blinded trial comparing the effects of premedication with 0.5 mg/kg oral midazolam versus 1 μg/kg intranasal dexmedetomidine in children between 2 and 12 years undergoing abdominal surgery. Sedation scores at separation and induction were the primary outcome measures. Behaviour scores and haemodynamic changes were secondary outcomes. Student's t-test and Chi-square were used for analysis of the variables. Results: Sedation scores were superior in Group B (dexmedetomidine) than Group A (midazolam) at separation and induction (P < 0.001).The behaviour scores at separation, induction and wake up scores at extubation were similar between the two groups. The heart rate and blood pressure showed significant differences at 15, 30 and 45 min in Group B but did not require pharmacological intervention for correction. Conclusion: Intranasal dexmedetomidine at a dose of 1 μg/kg produced superior sedation scores at separation and induction but normal behavioural scores in comparison to oral midazolam in paediatric patients.